GREEN SUPPLY CHAIN PRACTICES FRAMEWORK FOR PETROCHEMICALS IN EGYPT - Karim Soliman; Ghada El-Kady (Renewable Energy and Sustainable Development)
The aim of this study is to determine the extent of green supply chain management (GSCM) practices used by Shell and Co-operation (Co-op) Petroleum Companies in Egypt and to evaluate the effect of GSCM practices on the operational performance of both companies. A conceptual framework was developed to link the GSCM practices and operational performance. The framework consisted of three GSCM practices (green procurement, green manufacturing, and reverse logistics) as independent variables and four operational attributes (quality, safety, delivery, and flexibility) as dependent variables. The data was collected through on-site surveys, using eighteen-item-questionnaire with the relevant departments in both companies from the three managerial levels (i.e. strategic, tactical, and operational). Further, the results, based on benchmarking, were statistically analyzed by Fischer analysis. The results offer guidelines to petroleum and lubricant manufacturers to enhance their operational performance and customer satisfaction while employing GSCM practices throughout their entire supply chain (SC).